History of microfinance in Bangladesh: A life cycle theory approach. Issue 4 (19th May 2019) - Mia, Md Aslam; Lee, Hwok-Aun; Chandran, VGR; Rasiah, Rajah; Rahman, Mahfuzur
Abstract: This study aims to conceptualise and document the historical evolution of microfinance in Bangladesh using the life cycle theory (LCT). Based on the LCT nomenclature, the microfinance sector in Bangladesh shows characteristics broadly consistent with the saturation phase (2006–2015) – which potentially has adverse impacts on both microfinance clients and institutions. The maturity phase (1996–2005) of microfinance has corresponded with competition and several innovations (financial and non-financial). However, the saturation phase sees increasing presence of uncoordinated microfinance institutions and expansion of multiple borrowing, as well as commercialisation and 'mission drift', which constitute important challenges for the regulatory authority and management of microfinance institutions.